Doped sodium electric precursor and preparation method and application thereof

By preparing doped sodium battery precursors through a one-step spray pyrolysis method, the problems of high cost and high energy consumption of sodium-ion battery cathode materials have been solved, the material composition uniformity and structural stability have been improved, and the electrochemical performance has been significantly enhanced.

CN121405152APending Publication Date: 2026-01-27JINGMEN GEM NEW MATERIAL CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511549077.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-28
Publication Date
2026-01-27

AI Technical Summary

Technical Problem

Existing sodium-ion battery layered oxide cathode materials have high manufacturing costs, high energy consumption, poor compositional uniformity and structural stability, which affect electrochemical performance.

Method used

A one-step spray pyrolysis method was used to prepare doped sodium-ion battery precursors. By mixing a nickel-manganese-iron mixed salt solution with the doping metal salt, uniform atomic-level doping of multiple elements was achieved, reducing energy consumption and improving the material composition uniformity and structural stability.

Benefits of technology

This significantly reduces the manufacturing cost of sodium-ion battery cathode materials, improves their rate performance and cycle stability, and achieves efficient and low-cost material preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a doped sodium electric precursor as well as a preparation method and application thereof. The preparation method comprises the following steps that a nickel-manganese-iron mixed salt solution and doped metal salt are mixed, and a mixed solution is obtained; wherein doped metal ions in the doped metal salt comprise titanium ions, magnesium ions and zinc ions; and carrying out spray pyrolysis on the mixed solution to obtain the doped sodium electric precursor. The preparation method provided by the invention is simple in process, the doped sodium electric precursor with the characteristics of high entropy effect and the like can be directly prepared through one-step spray pyrolysis, the efficiency is high, the energy consumption is low, and the cost advantage is obvious; in addition, the process route also realizes uniform atomic-scale doping of various elements. The sodium ion layered oxide positive electrode material prepared based on the method is uniform in component and stable in structure, and the rate capability and the cycling stability of the sodium ion layered oxide positive electrode material are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of sodium-ion battery technology, specifically relating to a doped sodium battery precursor, its preparation method, and its application. Background Technology

[0002] Sodium-ion batteries have broad application prospects in the start-stop battery market, and their large-scale application has become an inevitable trend. However, the current persistently low price of lithium resources has objectively slowed down the pace of industrial expansion of sodium-ion batteries and posed a more severe challenge to the cost control capabilities of sodium-ion batteries. For sodium-ion batteries, sodium-ion layered oxide cathode materials mainly rely on the process route of "co-precipitation process - mixing (sodium source) - high-temperature calcination - finished product". This route has exposed many defects in actual production: 1) High raw material cost: the co-precipitation method requires high purity of metal salts such as nickel, cobalt, and manganese, and the process is complex and energy-intensive; 2) High energy consumption; 3) Difficulty in controlling sodium source volatilization loss and uniformity: sodium source is prone to volatilization during high-temperature calcination, leading to deviations in stoichiometry and poor product consistency. Furthermore, solid-phase mixing makes it difficult to ensure the uniform distribution of sodium elements in precursor particles; 4) Complex phase structure control: the phase transition behavior during calcination is extremely sensitive to parameter changes, making batch stability control difficult; 5) Irregular product morphology, affecting electrode compaction density and energy density. The aforementioned defects have hindered the widespread adoption and expansion of sodium-ion batteries in the field of start-stop batteries.

[0003] Existing technologies have addressed these shortcomings. For example, CN115377409A discloses a method for preparing high-performance layered oxide electrode materials for sodium-ion batteries. The first step involves mixing sodium, nickel, zinc, iron, manganese, and titanium sources in a specific ratio using high-energy ball milling, followed by vacuum drying to obtain precursor powder. The second step involves calcining the precursor powder at high temperature followed by quenching to obtain the high-performance layered oxide electrode material for sodium-ion batteries. However, this existing technology uses high-energy ball milling, not atomic-level mixing, which may result in uneven distribution of the precursor powder. Furthermore, the stepwise operation of ball milling followed by calcination increases energy consumption, and using high-purity raw materials is not conducive to cost control in sodium-ion batteries.

[0004] Therefore, how to effectively reduce the manufacturing cost and energy consumption of sodium ion layered oxide cathode materials, while simultaneously improving the compositional uniformity, structural stability, and electrochemical performance of the products, is an urgent technical problem to be solved. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the present invention aims to provide a doped sodium electrode precursor, its preparation method, and its applications. The preparation method provided by this invention is simple, directly preparing a doped sodium electrode precursor with high entropy effects through a one-step spray pyrolysis process. This method is not only highly efficient but also low in energy consumption, offering significant cost advantages. Furthermore, this process route achieves uniform atomic-level doping of multiple elements. The resulting sodium-ion layered oxide cathode material exhibits uniform composition and stable structure, with significantly improved rate performance and cycle stability.

[0006] To achieve this objective, the present invention adopts the following technical solution:

[0007] In a first aspect, the present invention provides a method for preparing a doped sodium battery precursor, the method comprising the following steps:

[0008] A mixed solution is obtained by mixing a nickel-manganese-iron mixed salt solution with a doped metal salt; wherein the doped metal ions in the doped metal salt include titanium ions, magnesium ions and zinc ions.

[0009] The mixed solution was subjected to spray pyrolysis to obtain the doped sodium-ion precursor.

[0010] The preparation method provided by this invention is simple, and a doped sodium electrode precursor with high entropy effect and other characteristics can be directly prepared through a one-step spray pyrolysis process. This method is not only highly efficient but also has low energy consumption and significant cost advantages. Furthermore, this process route achieves uniform atomic-level doping of multiple elements. The sodium-ion layered oxide cathode material prepared in this way has uniform composition and stable structure, and its rate performance and cycle stability are significantly improved.

[0011] Preferably, the nickel sulfate and manganese sulfate are obtained by high-pressure acid leaching of laterite nickel ore.

[0012] Preferably, the ferrous sulfate is derived from a byproduct of the titanium dioxide production process.

[0013] In this invention, the above-mentioned raw material sources are selected, which are relatively inexpensive and can significantly reduce the manufacturing cost of layered oxide cathode materials for sodium-ion batteries. Moreover, it realizes the high-value utilization of industrial by-products (ferrous sulfate) and effectively utilizes abundant low-grade laterite nickel ore resources, which greatly reduces energy consumption and carbon emissions in the raw material production process, reflecting the social demand for resource recycling and environmental benefits.

[0014] Preferably, the ferrous sulfate contains titanium, and the content of titanium is ≤0.5wt%, for example, it can be 0.5wt%, 0.4wt%, 0.3wt%, 0.2wt%, 0.1wt%, or 0, etc.

[0015] Preferably, the nickel sulfate and manganese sulfate contain magnesium, and the content of magnesium is less than or equal to 0.02 wt% of the total mass of the nickel sulfate and manganese sulfate. For example, the content of magnesium may be 0.02 wt%, 0.01 wt%, or 0.

[0016] In this invention, ferrous sulfate, nickel sulfate, and manganese sulfate inevitably contain some impurities. These impurities can work synergistically with the added dopant metal ions in the synthesis of the doped sodium-ion battery precursor: in-situ doping and impurity upscaling. Impurities such as titanium and magnesium can be effectively utilized as in-situ dopants, avoiding the additional purification costs incurred by impurity removal and achieving upscaling of impurity elements. Therefore, this composite doping achieved by the combination of inherent impurities and controllable addition of dopant metal ions helps to synergistically optimize the crystal structure stability and ion / electron transport characteristics of the subsequently prepared sodium-ion layered oxide cathode material, thereby significantly improving the cycle stability, rate performance, and overall electrochemical performance of the cathode material.

[0017] Preferably, in the nickel-manganese-iron mixed salt solution, the molar ratio of nickel ions, manganese ions, and ferrous ions is (15-75):(0-75):(15-40), wherein the range of nickel ions "15-75" can be, for example, 15, 25, 33.4, 35, 45, 65, or 75, the range of manganese ions "0-75" can be, for example, 5, 10, 20, 30, 33.3, 40, 50, 60, or 70, and the range of ferrous ions "15-40" can be, for example, 15, 20, 25, 30, 33.3, 35, or 40.

[0018] Preferably, in the nickel-manganese-iron mixed salt solution, nickel ions, manganese ions and ferrous ions are collectively referred to as main element metal ions, and the mass concentration of the main element metal ions is 100-400 g / L, for example, it can be 100 g / L, 200 g / L, 300 g / L or 400 g / L, etc.

[0019] In this invention, the mass concentration of the main element metal ions is 100-400 g / L, which can effectively improve the efficiency of large-scale production and reduce energy consumption.

[0020] Preferably, based on the total mass of the main element metal ions, the mass fractions of doped titanium ions, magnesium ions, and zinc ions in the mixed solution meet the following requirements:

[0021] 0<ω Ti ≤5000ppm, for example, it can be 500ppm, 1000ppm, 2000ppm, 3000ppm, 4000ppm, or 5000ppm, etc., 0<ω Mg≤8000ppm, for example, it can be 500ppm, 1000ppm, 2000ppm, 3000ppm, 4000ppm, 5000ppm, 6000ppm, 7000ppm, or 8000ppm, etc., 0<ω Zn ≤8000ppm, for example, it can be 500ppm, 1000ppm, 2000ppm, 3000ppm, 4000ppm, 5000ppm, 6000ppm, 7000ppm or 8000ppm, etc.

[0022] Preferably, the spray pyrolysis includes the steps of solution atomization and pyrolysis.

[0023] Preferably, the droplet size D50 after atomization of the solution is ≤100μm, for example, it can be 100μm, 90μm, 80μm, 70μm, 60μm, 50μm, 40μm, 30μm, 20μm, 10μm, 5μm or 1μm, etc.

[0024] Preferably, the pyrolysis temperature is 750-1100℃, for example, it can be 750℃, 800℃, 850℃, 900℃, 950℃, 1000℃, 1050℃ or 1100℃, etc.

[0025] In this invention, a suitable pyrolysis temperature helps the multi-metal solution to fully pyrolyze, thereby improving the yield.

[0026] Preferably, during the solution atomization process, the atomization feed flow rate is 20-40 L / h, for example, it can be 20 L / h, 30 L / h, 32 L / h, 34 L / h, 36 L / h, 38 L / h or 40 L / h, etc.

[0027] Preferably, the solution is atomized by pneumatic atomization and / or ultrasonic atomization.

[0028] Preferably, when the pneumatic atomization is performed, the pressure of the high-pressure gas is 0.3-1.2 MPa, for example, it can be 0.3 MPa, 0.5 MPa, 0.7 MPa, 0.9 MPa, 1 MPa, or 1.2 MPa. For example, the high-pressure gas can be compressed air.

[0029] Preferably, the atomized feed flow rate and the gas pressure satisfy the following relationship:

[0030] 0.1≤a / b≤0.5, where a is the atomized feed flow rate and b is the gas pressure of the high-pressure gas.

[0031] In this invention, 0.1 ≤ a / b ≤ 0.5, for example, it can be 0.1, 0.2, 0.3, 0.4 or 0.5, etc.

[0032] In this invention, by defining the above-mentioned relationship, the atomizing feed flow rate and the high-pressure gas pressure are coupled and controlled, which helps to obtain atomized droplets with uniform particle size distribution and concentrated size, improves atomization stability, avoids atomization instability caused by flow or pressure fluctuations, ensures continuous and stable operation of the spraying process, and lays the foundation for batch repeatability. The uniform size and concentrated distribution of atomized droplets greatly reduce the reaction asynchrony caused by droplet size differences during pyrolysis, ensuring the uniformity of composition, morphology and particle size of particles in the precursor, which helps to optimize the rate performance and cycle stability of sodium ion layered oxide cathode materials.

[0033] Preferably, the droplet size D50 after the solution is atomized is 3-8 μm, for example, it can be 3 μm, 4 μm, 5 μm, 6 μm, 7 μm or 8 μm, etc.

[0034] Preferably, the droplet size distribution (D90-D10) / D50 after atomization of the solution is ≤0.8, for example, it can be 0.8, 0.75, 0.7, 0.6, 0.65 or 0.5, etc.

[0035] In this invention, the droplet size distribution (D90-D10) / D50 after solution atomization is ≤0.8, indicating that the atomized droplets are highly uniform in size. This allows them to undergo highly synchronized solvent evaporation, precursor decomposition, nucleation, and crystal growth kinetics during pyrolysis, greatly eliminating the non-uniformity of reaction rates caused by droplet size differences. This lays the foundation for product uniformity. Based on this, the doped sodium-ion precursor prepared exhibits excellent consistency in morphology and particle size distribution, and the dopant elements are evenly distributed in the particles.

[0036] Preferably, the atmosphere for pyrolysis is an oxygen-containing atmosphere. For example, it can be an air or oxygen atmosphere.

[0037] Preferably, the pyrolysis time is 8-12 hours, for example, 8 hours, 10 hours or 12 hours.

[0038] Preferably, the temperature of the pyrolysis varies in a gradient along the direction of movement of the atomized droplets.

[0039] The present invention employs the aforementioned temperature variation method for the pyrolysis process, which can precisely match the multi-stage reaction requirements of the atomized droplets. This not only significantly improves the overall efficiency and energy utilization of the pyrolysis reaction and effectively avoids the problems of local overheating or incomplete reaction, but also helps to precisely control the nucleation and growth process of the product, thereby significantly improving the uniformity of the product's particle size, morphological regularity, crystallinity, and chemical composition, ultimately obtaining a sodium-ion battery cathode material with superior physicochemical properties.

[0040] Preferably, a preheating step is performed between solution atomization and pyrolysis.

[0041] Preferably, the preheating temperature is 350-500℃, for example, it can be 350℃, 400℃, 450℃ or 500℃.

[0042] In this invention, the purpose of preheating in the range of 350-500℃ is to achieve effective evaporation of the solvent and preliminary removal or decomposition of some volatile components, thus laying a uniform and stable reaction foundation for subsequent gradient pyrolysis.

[0043] Preferably, the preparation method includes the following steps:

[0044] (1) Nickel sulfate, manganese sulfate and ferrous sulfate are added to deionized water in a molar ratio of (15-75):(0-75):(15-40) to obtain a nickel-manganese-iron mixed salt solution; wherein, in the nickel-manganese-iron mixed salt solution, nickel ions, manganese ions and ferrous ions are collectively referred to as main element metal ions, and the mass concentration of the main element metal ions is 100-400 g / L; the nickel sulfate and manganese sulfate are obtained by high-pressure acid leaching and refining of laterite nickel ore; the ferrous sulfate is derived from the by-product of titanium dioxide production process; the ferrous sulfate contains titanium element, and the content of titanium element is ≤0.5wt%; the nickel sulfate and manganese sulfate contain magnesium element, and the content of magnesium element is less than or equal to 0.02wt% of the total mass of the nickel sulfate and manganese sulfate.

[0045] (2) Under stirring conditions, a doped metal salt is added to the nickel-manganese-iron mixed salt solution for mixing to obtain a mixed solution; wherein the doped metal salt includes titanium sulfate, magnesium sulfate and zinc sulfate; based on the total mass of the main element metal ions, the mass fractions of doped titanium ions, magnesium ions and zinc ions in the mixed solution meet the following requirements: 0 < ω Ti ≤5000ppm, 0<ω Mg ≤8000ppm, 0<ω Zn ≤8000ppm.

[0046] (3) The mixed solution is subjected to spray pyrolysis, which includes sequential steps of solution atomization, preheating and pyrolysis, and a doped sodium battery precursor is obtained after the process; wherein, during the solution atomization process, the atomization feed flow rate is 20-40 L / h; the solution atomization method is pneumatic atomization, the compressed air pressure is 0.3-1.2 MPa, and the atomization feed flow rate and the gas pressure satisfy the following relationship: 0.1≤a / b≤0.5, where a is the atomization feed flow rate and b is the high-pressure gas pressure; the preheating temperature is 350-500℃, and the preheating time is 2-4h (e.g., 2h, 3h or 4h, etc.); the pyrolysis atmosphere is an oxygen-containing atmosphere, the pyrolysis temperature range is 750-1100℃, the pyrolysis temperature varies gradient along the movement direction of the atomized droplets, and the pyrolysis time is 8-12h.

[0047] It should be noted that the products after spray pyrolysis are collected through a collection chamber, which consists of an airflow crusher and a bag filter, and is equipped with a tail gas absorption device and a water curtain dust removal tower, thereby ensuring closed-loop production of the entire synthesis process of the doped sodium-ion precursor.

[0048] In a second aspect, the present invention provides a doped sodium-electric precursor, which is prepared by the preparation method described in the first aspect.

[0049] Thirdly, the present invention provides a sodium-ion battery, wherein the positive electrode of the sodium-ion battery includes a sodium-ion battery positive electrode material, and the sodium-ion battery positive electrode material is obtained by sintering a sodium source and a doped sodium battery precursor as described in the second aspect.

[0050] For example, the sodium source may be sodium carbonate, sodium hydroxide, or sodium nitrate.

[0051] Preferably, the sintering atmosphere includes an oxygen-containing atmosphere, for example, an air atmosphere or an oxygen atmosphere.

[0052] Preferably, the sintering temperature is 750-1100℃, for example, 750℃, 850℃, 900℃, 950℃, 1000℃ or 1100℃, and the time is 8-12h, for example, 8h, 9h, 10h, 11h or 12h.

[0053] The numerical range described in this invention includes not only the point values ​​listed above, but also any point values ​​within the numerical ranges not listed above. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific point values ​​included in the range.

[0054] Compared with the prior art, the present invention has the following beneficial effects:

[0055] The preparation method provided by this invention is simple, and a doped sodium electrode precursor with high entropy effect and other characteristics can be directly prepared through a one-step spray pyrolysis process. This method is not only highly efficient but also has low energy consumption and significant cost advantages. Furthermore, this process route achieves uniform atomic-level doping of multiple elements. The sodium-ion layered oxide cathode material prepared in this way has uniform composition and stable structure, and its rate performance and cycle stability are significantly improved. Detailed Implementation

[0056] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention.

[0057] Example 1

[0058] This embodiment provides a method for preparing a doped sodium battery precursor, the method comprising the following steps:

[0059] (1) Nickel sulfate, manganese sulfate and ferrous sulfate are added to deionized water in a molar ratio of 1:1:1 to obtain a nickel-manganese-iron mixed salt solution; wherein, in the nickel-manganese-iron mixed salt solution, nickel ions, manganese ions and ferrous ions are collectively referred to as main element metal ions, and the mass concentration of the main element metal ions is 120 g / L; the nickel sulfate and manganese sulfate are obtained by high-pressure acid leaching and refining of laterite nickel ore; the ferrous sulfate is derived from a by-product of the titanium dioxide production process; the ferrous sulfate contains impurity titanium, and the content of impurity titanium is ≤0.5 wt%; the nickel sulfate and manganese sulfate contain impurity magnesium, and the content of impurity magnesium is less than or equal to 0.02 wt% of the total mass of the nickel sulfate and manganese sulfate.

[0060] (2) Under stirring conditions, a doped metal salt is added to the nickel-manganese-iron mixed salt solution for mixing to obtain a mixed solution; wherein the doped metal salt includes titanium sulfate, magnesium sulfate, and zinc sulfate; based on the total mass of the main element metal ions, the mass fractions of doped titanium ions, magnesium ions, and zinc ions in the mixed solution meet the following requirements: ω Ti =3000ppm, ω Mg =3000ppm, ω Zn =2000ppm.

[0061] (3) The mixed solution is subjected to spray pyrolysis, which includes sequential steps of solution atomization and pyrolysis, and a doped sodium battery precursor is obtained after the process is completed; wherein, during the solution atomization process, the atomization feed flow rate is 32 L / h; the solution atomization method is pneumatic atomization, and the compressed air pressure is 0.3 MPa; the droplet size D50 after solution atomization is 8 μm; the pyrolysis atmosphere is air atmosphere, the pyrolysis temperature is 1100℃, and the pyrolysis time is 12 h.

[0062] This embodiment also provides a doped sodium-electric precursor, which is prepared by the preparation method described above.

[0063] This embodiment also provides a sodium-ion battery cathode material, which is obtained by uniformly mixing sodium carbonate and the doped sodium battery precursor as described above at a molar ratio of 1.08:1, and then sintering in an oxygen atmosphere at 1100°C for 12 hours.

[0064] Example 2

[0065] This embodiment provides a method for preparing a doped sodium battery precursor, the method comprising the following steps:

[0066] (1) Nickel sulfate, manganese sulfate and ferrous sulfate are added to deionized water in a molar ratio of 1:1:1 to obtain a nickel-manganese-iron mixed salt solution; wherein, in the nickel-manganese-iron mixed salt solution, nickel ions, manganese ions and ferrous ions are collectively referred to as main element metal ions, and the mass concentration of the main element metal ions is 250 g / L; the nickel sulfate and manganese sulfate are obtained by high-pressure acid leaching and refining of laterite nickel ore; the ferrous sulfate is derived from a by-product of the titanium dioxide production process; the ferrous sulfate contains impurity titanium, and the content of the impurity titanium is ≤0.5 wt%; the nickel sulfate and manganese sulfate contain impurity magnesium, and the content of the impurity magnesium is less than or equal to 0.02 wt% of the total mass of the nickel sulfate and manganese sulfate.

[0067] (2) Under stirring conditions, a doped metal salt is added to the nickel-manganese-iron mixed salt solution for mixing to obtain a mixed solution; wherein the doped metal salt includes titanium sulfate, magnesium sulfate, and zinc sulfate; based on the total mass of the main element metal ions, the mass fractions of doped titanium ions, magnesium ions, and zinc ions in the mixed solution meet the following requirements: ω Ti =2000ppm, ω Mg =2000ppm, ω Zn =4000ppm.

[0068] (3) The mixed solution is subjected to spray pyrolysis, which includes sequential steps of solution atomization and pyrolysis, and a doped sodium battery precursor is obtained after the process is completed; wherein, during the solution atomization process, the atomization feed flow rate is 35 L / h; the solution atomization method is pneumatic atomization, and the compressed air pressure is 0.8 MPa; the droplet size D50 after solution atomization is 5 μm; the pyrolysis atmosphere is air atmosphere, the pyrolysis temperature is 900℃, and the pyrolysis time is 10 h.

[0069] This embodiment also provides a doped sodium-electric precursor, which is prepared by the preparation method described above.

[0070] This embodiment also provides a sodium-ion battery cathode material, which is obtained by uniformly mixing sodium carbonate and the doped sodium battery precursor as described above at a molar ratio of 1.08:1, and then sintering in an oxygen atmosphere at 900°C for 10 hours.

[0071] Example 3

[0072] This embodiment provides a method for preparing a doped sodium battery precursor, the method comprising the following steps:

[0073] (1) Nickel sulfate, manganese sulfate and ferrous sulfate are added to deionized water in a molar ratio of 1:1:1 to obtain a nickel-manganese-iron mixed salt solution; wherein, in the nickel-manganese-iron mixed salt solution, nickel ions, manganese ions and ferrous ions are collectively referred to as main element metal ions, and the mass concentration of the main element metal ions is 400 / L; the nickel sulfate and manganese sulfate are obtained by high-pressure acid leaching and refining of laterite nickel ore; the ferrous sulfate is derived from a by-product of the titanium dioxide production process; the ferrous sulfate contains impurity titanium, and the content of the impurity titanium is ≤0.5wt%; the nickel sulfate and manganese sulfate contain impurity magnesium, and the content of the impurity magnesium is less than or equal to 0.02wt% of the total mass of the nickel sulfate and manganese sulfate.

[0074] (2) Under stirring conditions, a doped metal salt is added to the nickel-manganese-iron mixed salt solution for mixing to obtain a mixed solution; wherein the doped metal salt includes titanium sulfate, magnesium sulfate, and zinc sulfate; based on the total mass of the main element metal ions, the mass fractions of doped titanium ions, magnesium ions, and zinc ions in the mixed solution meet the following requirements: ω Ti =1000ppm, ω Mg =4000ppm, ω Zn =4000ppm.

[0075] (3) The mixed solution is subjected to spray pyrolysis, which includes the steps of solution atomization and pyrolysis performed sequentially, and a doped sodium battery precursor is obtained after the process is completed; wherein, during the solution atomization process, the atomization feed flow rate is 40 L / h; the solution atomization method is pneumatic atomization, and the compressed air pressure is 1.2 MPa; the droplet size D50 of the solution after atomization is 3 μm; the pyrolysis atmosphere is air atmosphere, the pyrolysis temperature is 850℃, and the pyrolysis time is 8 h.

[0076] This embodiment also provides a doped sodium-electric precursor, which is prepared by the preparation method described above.

[0077] This embodiment also provides a sodium-ion battery cathode material, which is obtained by uniformly mixing sodium carbonate and the doped sodium battery precursor as described above at a molar ratio of 1.08:1, and then sintering in an oxygen atmosphere at 850°C for 8 hours.

[0078] Example 4

[0079] The difference between this embodiment and Embodiment 1 is that the values ​​of the atomizing feed flow rate and the gas pressure are adjusted so that the atomizing feed flow rate and the gas pressure satisfy the following relationship: a / b=0.2, where a is the atomizing feed flow rate and b is the gas pressure of the high-pressure gas; the droplet size D50 of the solution after atomization is 7μm, and the droplet size distribution (D90-D10) / D50=0.7.

[0080] The remaining preparation methods and parameters are consistent with those in Example 1.

[0081] Example 5

[0082] The difference between this embodiment and Embodiment 1 is that the values ​​of the atomizing feed flow rate and the gas pressure are adjusted so that the atomizing feed flow rate and the gas pressure satisfy the following relationship: a / b=0.3, where a is the atomizing feed flow rate and b is the gas pressure of the high-pressure gas; the droplet size D50 of the solution after atomization is 5μm, and the droplet size distribution (D90-D10) / D50=0.8.

[0083] The remaining preparation methods and parameters are consistent with those in Example 1.

[0084] Example 6

[0085] The difference between this embodiment and Embodiment 1 is that the values ​​of the atomizing feed flow rate and the gas pressure are adjusted so that the atomizing feed flow rate and the gas pressure satisfy the following relationship: a / b=0.5, where a is the atomizing feed flow rate and b is the gas pressure of the high-pressure gas; the droplet size D50 of the solution after atomization is 4μm, and the droplet size distribution (D90-D10) / D50=0.6.

[0086] The remaining preparation methods and parameters are consistent with those in Example 1.

[0087] Example 7

[0088] The difference between this embodiment and Embodiment 1 is that the pyrolysis temperature increases gradually along the direction of movement of the atomized droplets, and the pyrolysis temperature range is 750-1100℃.

[0089] The remaining preparation methods and parameters are consistent with those in Example 1.

[0090] Example 8

[0091] The difference between this embodiment and embodiment 7 is that a preheating step is performed between the solution atomization and pyrolysis. The preheating temperature is 400°C and the time is 2 hours.

[0092] The remaining preparation methods and parameters are consistent with those in Example 7.

[0093] Example 9

[0094] The difference between this embodiment and Embodiment 1 is that the mass fraction of doped titanium ions in the mixed solution is 6000 ppm.

[0095] The remaining preparation methods and parameters are consistent with those in Example 1.

[0096] Example 10

[0097] The difference between this embodiment and Embodiment 1 is that the mass fraction of magnesium ions in the mixed solution is 9000 ppm.

[0098] The remaining preparation methods and parameters are consistent with those in Example 1.

[0099] Example 11

[0100] The difference between this embodiment and Embodiment 1 is that the mass fraction of zinc ions in the mixed solution is 9000 ppm.

[0101] The remaining preparation methods and parameters are consistent with those in Example 1.

[0102] Example 12

[0103] The difference between this embodiment and embodiment 4 is that a / b = 0.08.

[0104] The remaining preparation methods and parameters are consistent with those in Example 4.

[0105] Example 13

[0106] The difference between this embodiment and embodiment 4 is that a / b = 0.8.

[0107] The remaining preparation methods and parameters are consistent with those in Example 4.

[0108] Example 14

[0109] The difference between this embodiment and embodiment 8 is that the preheating temperature is 300°C.

[0110] The remaining preparation methods and parameters are consistent with those in Example 8.

[0111] Example 15

[0112] The difference between this embodiment and Embodiment 1 is that the nickel sulfate and manganese sulfate mentioned are both commercially available, commodity-grade raw materials.

[0113] The remaining preparation methods and parameters are consistent with those in Example 1.

[0114] Example 16

[0115] The difference between this embodiment and Embodiment 1 is that the ferrous sulfate is replaced with pure reagent-grade ferrous sulfate that is not derived from titanium dioxide.

[0116] The remaining preparation methods and parameters are consistent with those in Example 1.

[0117] Example 17

[0118] The difference between this embodiment and Embodiment 1 is that the ferrous sulfate is replaced with commercially available commercial-grade ferric sulfate.

[0119] The remaining preparation methods and parameters are consistent with those in Example 1.

[0120] Comparative Example 1

[0121] The difference between this comparative example and Example 1 is that the doped metal salt in step (2) does not contain titanium sulfate.

[0122] The remaining preparation methods and parameters are consistent with those in Example 1.

[0123] Comparative Example 2

[0124] The difference between this comparative example and Example 1 is that the doped metal salt in step (2) does not contain magnesium sulfate.

[0125] The remaining preparation methods and parameters are consistent with those in Example 1.

[0126] Comparative Example 3

[0127] The difference between this comparative example and Example 1 is that the doped metal salt in step (2) does not contain zinc sulfate.

[0128] The remaining preparation methods and parameters are consistent with those in Example 1.

[0129] Comparative Example 4

[0130] The difference between this comparative example and Example 1 is that step (2) is not performed.

[0131] The remaining preparation methods and parameters are consistent with those in Example 1.

[0132] Performance testing

[0133] The sodium-ion battery is prepared based on the sodium-ion battery cathode material provided in the above embodiments and comparative examples. The specific steps include:

[0134] A positive electrode sheet was prepared using the above-mentioned sodium-ion battery positive electrode material as the main positive electrode material, and a metallic sodium sheet was used as the negative electrode sheet. A glass fiber separator was used, and the electrolyte consisted of 1 mol / L sodium hexafluorophosphate and a mixed solvent of ethylene carbonate and diethyl carbonate in a volume ratio of 1:1. The CR2032 coin cell was then assembled.

[0135] Cycle performance and rate performance were tested on the CR2032 coin cells described above. The cycle performance test involved measuring the capacity retention of the samples after 300 cycles at 1C. The rate performance test involved conducting 300 charge-discharge cycles at 5C with different cathode materials under a voltage platform of 3.2-3.5V, recording the discharge specific capacity of different samples at 5C. The test results are shown in Table 1.

[0136] Table 1

[0137]

[0138] analyze:

[0139] As shown in Table 1, the preparation method provided by this invention is simple, and a doped sodium electrode precursor with high entropy effect and other characteristics can be directly prepared through a one-step spray pyrolysis process. This method is not only highly efficient but also has low energy consumption and significant cost advantages. Furthermore, this process route achieves uniform atomic-level doping of multiple elements. The sodium ion layered oxide cathode material prepared in this way has uniform composition and stable structure, and its rate performance and cycle stability are significantly improved.

[0140] A comparison of Examples 1 and 4-6 shows that by defining the above-mentioned relationship, the atomizing feed flow rate and the gas pressure of the high-pressure gas are coupled and controlled, which helps to obtain atomized droplets with uniform particle size distribution and concentrated size, improves atomization stability, avoids atomization instability caused by flow or pressure fluctuations, ensures continuous and stable operation of the spraying process, and lays the foundation for batch repeatability. The uniform size and concentrated distribution of atomized droplets greatly reduce the reaction asynchrony caused by droplet size differences during pyrolysis, ensuring the uniformity of the composition, morphology and particle size of the particles in the precursor, which helps to optimize the rate performance and cycle stability of sodium ion layered oxide cathode materials.

[0141] A comparison of Examples 1 and 7 shows that the pyrolysis process using the above-mentioned temperature variation method can accurately match the multi-stage reaction requirements of the atomized droplets. This not only significantly improves the overall efficiency and energy utilization of the pyrolysis reaction and effectively avoids the problems of local overheating or incomplete reaction, but also helps to accurately control the nucleation and growth process of the product, thereby significantly improving the uniformity of the product's particle size, morphological regularity, crystallinity, and chemical composition, ultimately obtaining a sodium-ion battery cathode material with better physicochemical properties.

[0142] A comparison of Examples 7 and 8 shows that introducing a preheating step at a specific temperature between solution atomization and pyrolysis helps to achieve effective solvent evaporation and preliminary removal or decomposition of some volatile components, laying a uniform and stable reaction foundation for subsequent gradient pyrolysis.

[0143] As can be seen from the comparison between Example 1 and Examples 9-11, if the mass fraction of doped titanium ions in the mixed solution is too high, it will lead to uneven element distribution in the material preparation, which is not conducive to improving cycle performance. If the mass fraction of doped magnesium ions and zinc ions in the mixed solution is too high, it will lead to uneven element distribution in the material preparation, and will also lead to a slight decrease in the positive electrode capacity, which is not conducive to improving the specific capacity.

[0144] A comparison of Examples 4 and 12-13 shows that if the a / b ratio is too small, the atomizing gas pressure will be relatively too high or the atomizing feed flow rate will be relatively too low, resulting in droplets that are too small. This leads to problems with evaporation / reaction kinetics and yield, incomplete reaction, uneven morphology, and low energy utilization, which is not conducive to cost reduction and efficiency improvement, and ultimately leads to a decline in the electrochemical performance of the sodium-ion battery cathode material. If the a / b ratio is too large, the atomizing gas pressure will be relatively too low or the atomizing feed flow rate will be relatively too high, resulting in droplets that are too large, leading to limitations in heat and mass transfer and process stability, resulting in uneven pyrolysis reaction, defective products, poor morphology, and a risk of reactor scaling, which is not conducive to cost reduction and efficiency improvement, and ultimately leads to a decline in the electrochemical performance of the sodium-ion battery cathode material.

[0145] A comparison between Example 8 and Example 14 shows that if the preheating temperature is too low, the product will have significant defects in its appearance, which will affect the rate performance.

[0146] A comparison of Examples 1 and 15-17 shows that if both nickel sulfate and manganese sulfate are commercially available raw materials, the impurities are relatively high, which will affect the rate performance; if ferrous sulfate is replaced with pure reagent-grade ferrous sulfate that is not derived from titanium dioxide, the cycle performance and rate performance are poor, and the cost is high; if ferrous sulfate is replaced with commercially available raw material ferric sulfate, the impurities are difficult to control, and the cycle performance and rate performance are poor.

[0147] As can be seen from the comparison between Example 1 and Comparative Examples 1-3, if the doped metal salt in step (2) does not contain titanium sulfate, the cycle performance will be worse; if the doped metal salt in step (2) does not contain magnesium sulfate, the cycle performance will be worse; if the doped metal salt in step (2) does not contain zinc sulfate, the rate performance will be worse.

[0148] As can be seen from the comparison between Example 1 and Comparative Example 4, the cycle performance and rate performance are the worst if no doped metal salt is introduced.

[0149] It should be noted that the technical solution of the present invention is illustrated through the above embodiments, but the present invention is not limited to the above embodiments, that is, it does not mean that the present invention must rely on the above embodiments to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a doped sodium-ion battery precursor, characterized in that, The preparation method includes the following steps: A mixed solution is obtained by mixing a nickel-manganese-iron mixed salt solution with a doped metal salt; wherein the doped metal ions in the doped metal salt include titanium ions, magnesium ions and zinc ions; The mixed solution was subjected to spray pyrolysis to obtain the doped sodium-ion precursor.

2. The preparation method according to claim 1, characterized in that, The nickel-manganese-iron mixed salt solution includes nickel sulfate, manganese sulfate, and ferrous sulfate; Preferably, the nickel sulfate and manganese sulfate are obtained by high-pressure acid leaching and refining of laterite nickel ore; Preferably, the ferrous sulfate is derived from a byproduct of the titanium dioxide production process; Preferably, the ferrous sulfate contains titanium, and the content of titanium is ≤0.5 wt%. Preferably, the nickel sulfate and manganese sulfate contain magnesium, and the content of magnesium is less than or equal to 0.02 wt% of the total mass of the nickel sulfate and manganese sulfate.

3. The preparation method according to claim 1 or 2, characterized in that, In the nickel-manganese-iron mixed salt solution, the molar ratio of nickel ions, manganese ions and ferrous ions is (15-75):(0-75):(15-40); Preferably, in the nickel-manganese-iron mixed salt solution, nickel ions, manganese ions and ferrous ions are collectively referred to as main element metal ions, and the mass concentration of the main element metal ions is 100-400 g / L.

4. The preparation method according to claim 3, characterized in that, Based on the total mass of the main element metal ions, the mass fractions of doped titanium ions, magnesium ions, and zinc ions in the mixed solution shall meet the following requirements: 0<ω Ti ≤5000ppm,0<ω Mg ≤8000ppm,0<ω Zn ≤8000ppm.

5. The preparation method according to any one of claims 1-4, characterized in that, The spray pyrolysis includes the steps of solution atomization and pyrolysis; Preferably, the droplet size D50 after atomization of the solution is ≤100μm; Preferably, the pyrolysis temperature is 750-1100℃.

6. The preparation method according to claim 5, characterized in that, During the solution atomization process, the atomization feed flow rate is 20-40 L / h; Preferably, the solution atomization method includes pneumatic atomization and / or ultrasonic atomization; Preferably, the pneumatic atomization method is such that the gas pressure of the high-pressure gas is 0.3-1.2 MPa during pneumatic atomization; Preferably, the atomized feed flow rate and the gas pressure satisfy the following relationship: 0.1≤a / b≤0.5, where a is the atomized feed flow rate and b is the gas pressure of the high-pressure gas; Preferably, the droplet size D50 after atomization of the solution is 3-8 μm; Preferably, the droplet size distribution (D90-D10) / D50 after atomization of the solution is ≤0.

8.

7. The preparation method according to claim 5 or 6, characterized in that, The atmosphere for pyrolysis is an oxygen-containing atmosphere; Preferably, the pyrolysis time is 8-12 hours; Preferably, the temperature of the pyrolysis varies in a gradient along the direction of movement of the atomized droplets; Preferably, a preheating step is performed between solution atomization and pyrolysis; Preferably, the preheating temperature is 350-500℃.

8. The preparation method according to any one of claims 1-6, characterized in that, The preparation method includes the following steps: (1) Nickel sulfate, manganese sulfate, and ferrous sulfate are added to deionized water in a molar ratio of (15-75):(0-75):(15-40) to obtain a nickel-manganese-iron mixed salt solution; wherein, in the nickel-manganese-iron mixed salt solution, nickel ions, manganese ions, and ferrous ions are collectively referred to as main element metal ions, and the mass concentration of the main element metal ions is 100-400 g / L; the nickel sulfate and manganese sulfate are obtained by high-pressure acid leaching and refining of laterite nickel ore; the ferrous sulfate is derived from a by-product of the titanium dioxide production process; the ferrous sulfate contains titanium element, and the content of titanium element is ≤0.5 wt%; the nickel sulfate and manganese sulfate contain magnesium element, and the content of magnesium element is less than or equal to 0.02 wt% of the total mass of the nickel sulfate and manganese sulfate; (2) Under stirring conditions, a doped metal salt is added to the nickel-manganese-iron mixed salt solution for mixing to obtain a mixed solution; wherein the doped metal salt includes titanium sulfate, magnesium sulfate and zinc sulfate; based on the total mass of the main element metal ions, the mass fractions of doped titanium ions, magnesium ions and zinc ions in the mixed solution meet the following requirements: 0 < ω Ti ≤5000ppm, 0<ω Mg ≤8000ppm, 0<ω Zn ≤8000ppm; (3) The mixed solution is subjected to spray pyrolysis, which includes sequential steps of solution atomization, preheating and pyrolysis, and a doped sodium battery precursor is obtained after the process. In the process of solution atomization, the atomization feed flow rate is 20-40 L / h. The solution atomization method is pneumatic atomization, and the gas pressure of the compressed air used is 0.3-1.2 MPa. The atomization feed flow rate and the gas pressure satisfy the following relationship: 0.1≤a / b≤0.5, where a is the atomization feed flow rate and b is the gas pressure of the high-pressure gas. The preheating temperature is 350-500℃ and the preheating time is 2-4 h. The pyrolysis atmosphere is an oxygen-containing atmosphere, the pyrolysis temperature range is 750-1100℃, the pyrolysis temperature changes gradient along the movement direction of the atomized droplets, and the pyrolysis time is 8-12 h.

9. A doped sodium-ion battery precursor, characterized in that, The doped sodium-ion precursor is prepared using the preparation method described in any one of claims 1-8.

10. A sodium-ion battery, characterized in that, The positive electrode of the sodium-ion battery includes a sodium-ion battery positive electrode material, which is obtained by sintering a sodium source and a doped sodium battery precursor as described in claim 9.

Citation Information

Patent Citations

  • High-performance sodium ion battery layered oxide electrode material

    CN115377409A